May Measurement Month 2019: an analysis of blood pressure screening results from Brazil. (20th May 2021) - Barbosa, Eduardo Costa Duarte; Feitosa, Audes M; Bortolotto, Luiz Aparecido; Guerra, Grazia Maria; Filho, Júlio César Ayres Ferreira; Cestário, Elizabeth E S; Yugar-Toledo, Juan Carlos; Pimentel, Rodrigo; Ferrari, Bruno; Aguiar, Rodrigo; Barroso, Weimar Kunz Sebba; Eibel, Bruna; et al.
Abstract: The aim of this study is to describe the results of the May Month Measurement (MMM) campaign implemented in Brazil, in 2019. Questionnaire data were collected and three measures of blood pressure (BP) were performed. The sample consisted of 13 476 individuals, 58.2% were white, 60.8% were women. The average age was 46.3 (18.6) years. Of all 13 476 participants, 6858 (50.9%) had hypertension defined as a systolic BP ≥140 mmHg or a diastolic BP ≥90 mmHg or being on anti-hypertensive medication. Of those with hypertension, 68.8% were aware of their diagnosis, 65.3% were on antihypertensive medication, and 36.1% had controlled BP (<140/90 mmHg). In addition, of 4479 participants on anti-hypertensive medication, 55.2% had controlled BP. The use of anti-hypertensive medication was associated with higher systolic ( P  < 0.001) and diastolic BP ( P  < 0.001) and having diabetes with higher systolic BP ( P  < 0.001). Previous hypertension in pregnancy was associated with higher systolic ( P  = 0.038) and diastolic BP ( P  = 0.003), and smoking was associated with higher systolic BP ( P  < 0.001). Lastly, obese and overweight individuals showed significantly higher systolic ( P  < 0.001) and diastolic ( P  < 0.001) BP. The Brazilian MMM19 data demonstrate that strategies to increase awareness of hypertension and a better control of the risk factors are still needed.